Safety and Efficacy of Enhanced Recovery after Surgery Protocol in Pediatric Patients Undergoing Hepato-Pancreatico-Biliary Surgery: A Prospective Randomized Control Study - Pujana Kanneganti; Anju Verma; Ankur Mandelia; Vijai Datta Upadhyaya; Basant Kumar; Tarun Kumar; Nishant Agarwal; Ashish Kannojia (Wolters Kluwer Medknow Publications, 2024)
Introduction: Enhanced recovery after surgery (ERAS) is a multidisciplinary approach to optimize patient care. The goal of this approach is to reduce the body's reaction to surgical stress by optimizing the perioperative nutritional status, promoting analgesia without opioids, and early postoperative feeding. In pediatric patients, very limited literature is available for the application of ERAS protocol. This study was done to evaluate the application of ERAS protocol in pediatric hepatobiliary and pancreatic patients. Materials and Methods: This is a randomized prospective study conducted over a period of 2 years at a tertiary center in North India. A total of 40 hepatobiliary and pancreatic patients who were willing to participate in the study were included in the study. Patients were randomized by computer-generated method and data were collected regarding demography, clinical diagnosis, preoperative and postoperative workup, and peri-operative care including analgesia, pain scores, postoperative recovery, hospital stay, and complications. These patients were followed for 6 months postoperatively and the results were evaluated using SPSS software. Results: The study included 20 patients each in both the conventional and ERAS group with median ages of 11.5 years and 7.1 years, respectively. The data analysis showed that the ERAS group of patients had better outcomes in terms of hospital stay and drain removal time with significant statistical differences. Pain scores and complications are almost the same in both groups. Conclusion: Principles of ERAS can be safely applied in pediatric patients undergoing major surgery in the present era of emerging infections and also increasing patient burden without morbidity.